Preterm infant growth velocity calculations: A systematic review (2017)
CONTEXT: Clinicians assess the growth of preterm infants and compare growth velocity using a variety of methods. OBJECTIVE: We determined the numerical methods used to describe weight, length, and head circumference growth velocity in preterm infants; these methods include grams/kilogram/ day (g/kg/d), grams/day (g/d), centimeters/week (cm/week), and change in z scores. DATA SOURCES: A search was conducted in April 2015 of the Medline database by using PubMed for studies that measured growth as a main outcome in preterm neonates between birth and hospital discharge and/or 40 weeks' postmenstrual age. English, French, German, and Spanish articles were included. The systematic review was conducted by using Preferred Reporting Items for Systematic Reviews and Meta-analyses methods. STUDY SELECTION: Of 1543 located studies, 373 (24%) calculated growth velocity. DATA EXTRACTION: We conducted detailed extraction of the 151 studies that reported g/kg/d weight gain velocity. RESULTS: A variety of methods were used. The most frequently used method to calculate weight gain velocity reported in the 1543 studies was g/kg/d (40%), followed by g/d (32%); 29% reported change in z score relative to an intrauterine or growth chart. In the g/kg/d studies, 39% began g/kg/d calculations at birth/admission, 20% at the start of the study, 10% at full feedings, and 7% after birth weight regained. The kilogram denominator was not reported for 62%. Of the studies that did report the denominators, the majority used an average of the start and end weights as the denominator (36%) followed by exponential methods (23%); less frequently used denominators included birth weight (10%) and an early weight that was not birth weight (16%). Nineteen percent (67 of 355 studies) made conclusions regarding extrauterine growth restriction or postnatal growth failure. Temporal trends in head circumference growth and length gain changed from predominantly cm/wk to predominantly z scores. LIMITATIONS AND CONCLUSIONS The lack of standardization of methods used to calculate preterm infant growth velocity makes comparisons between studies difficult and presents an obstacle to using research results to guide clinical practice.